The Polish Peasant in Europe and America. Some Remarks after One Hundred Years - Cersosimo, Giuseppina (Italian Sociological Review, 2020)
This paper presents how, one hundred years after its publication, The Polish Peasant in Europe and America, 1918-1920 still has relevance and specificity, providing food for discussion among social scientists, while providing insight for interpreting social phenomena. This paper will examine two aspects the methodological approach and the presence of women in migratory social phenomena and family.